Irradiation-Induced Heck Reaction of Unactivated Alkyl Halides at Room Temperature - Wang, Guang-Zu; Shang, Rui; Cheng, Wan-Min; Fu, Yao (Journal of the American Chemical Society, 2017)
The palladium-catalyzed Mizoroki–Heck reaction is arguably one of the most significant carbon–carbon bond-construction reactions to be discovered in the last 50 years, with a tremendous number of applications in the production of chemicals. This Nobel-Prize-winning transformation has yet to overcome the obstacle of its general application in a range of alkyl electrophiles, especially tertiary alkyl halides that possess eliminable β-hydrogen atoms. Whereas most palladium-catalyzed cross-coupling reactions utilize the ground-state reactivity of palladium complexes under thermal conditions and generally apply a single ligand system, we report that the palladium-catalyzed Heck reaction proceeds smoothly at room temperature with a variety of tertiary, secondary, and primary alkyl bromides upon irradiation with blue light-emitting diodes in the presence of a dual phosphine ligand system. We rationalize that this unprecedented transformation is achieved by utilizing the photoexcited-state reactivity of the palladium complex to enhance oxidative addition and suppress undesired β-hydride elimination.